The genus Scirtothrips in Australia (Insecta, Thysanoptera, Thripidae) - Hoddle, Mark S.; Mound, Laurence A. (Zootaxa, 2003)
Twenty-one species of leaf-feeding thrips from Australia in the genus Scirtothrips, including eleven newly described species, are here distinguished with an identification key and illustrations. Some of these species are host-specific, but with diverse host associations, including tree ferns, two different genera of cycads, Acacia, Allocasuarina, Brachychiton, Hakea, and Kunzea. Two new speciesgroups, based on S. albomaculatus and S. akakia, are distinguished, both with several species on endemic species of Acacia. In contrast, other species are highly polyphagous, and some of these are crop pests, including S. dorsalis and S. aurantii, the South African citrus thrips that was introduced recently to Queensland. Three species are part of the northern tropical fauna, S. dorsalis, S. dobroskyi, and S. tenor, whereas most of the others are endemic to the arid areas of Australia. The monotypic genus Labiothrips Bhatti & Mound is synonymised with Scirtothrips Shull, and the New Zealand species S. pan Palmer & Mound is removed from the Australian list as a misidentification. The species recognised are: S. akakia sp.n., S. albomaculatus Bianchi, S. astibos, sp.n., S. aurantii Faure, S. australiae Hood (=auricorpus Girault, syn.n.), S. casuarinae Palmer & Mound, S. dobroskyi Moulton, S. dorsalis Hood, S. drepanofortis sp. n., S. eremicus sp.n., S. frondis sp.n., S. helenae Palmer & Mound, S. inermis Priesner, S. kirrhos sp.n., S. litotes sp.n., S. longipennis (Bagnall), S. moneres sp.n., S. pilbara sp.n., S. quadriseta sp.n., S. solus sp.n., and S. tenor (Bhatti & Mound).